The genome sequence of the angle shades moth, Phlogophora meticulosa (Linnaeus, 1758) [version 1; peer review: 2 approved] - Douglas Boyes; Peter W.H. Holland (Wellcome Open Research, 2022)
We present a genome assembly from an individual female Phlogophora meticulosa (the angle shades; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 539 megabases in span. The majority of the assembly, 95.17%, is scaffolded into 31 chromosomal pseudomolecules, with the Z sex chromosome assembled. Some unassigned scaffolds are identified as belonging to the W chromosome based on half-depth coverage and comparison to other Noctuidae W chromosomes. The mitochondrial genome was also assembled and is 15.4 kilobases in length.